(Dis)Connected Generation - Amy Baldwin; Louis Nadelson; Dana Triblle (Journal of Effective Teaching in Higher Education)
College students have a variety of temptations that can keep them from making the most of their learning in and out of the classroom. Moreover, students’ habits and behaviors related to mobile device use can hinder their learning and can stymie faculty’s effective teaching practices. To explore these issues, we conducted a phenomenological study to examine first-year college students’ responses to questions about mobile devices to determine how faculty can improve classroom engagement. Findings included that students recognize the distraction that mobile devices have on their learning yet need more self-management skills to ensure that technology does not disrupt the focus required to learn. Students also revealed that they did not see the use of mobile devices in the classroom by other students as impeding their ability to learn. The implications of these results point to an opportunity to develop instructional strategies that can help students develop better self-regulation that could positively impact learning.